Non-abelian representations of some sporadic geometries - Ivanov, Alexander A. (2013)
For a point-line incidence system S =(P, L) with three points per line we define the universal representation group of S asR(S)= 〈zp, p∈P|zp^2=1 for p∈P,zp zq zr = 1 for {p,q,r} ∈ L〉We prove that if G is the 2-local parabolic geometry of the sporadic simple group F1(the Monster) or F2(the Baby Monster) thenR(G)≅F1or 2·F2, respectively.